2021
DOI: 10.3758/s13421-021-01264-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive mechanisms of statistical learning and segmentation of continuous sensory input

Abstract: Two classes of cognitive mechanisms have been proposed to explain segmentation of continuous sensory input into discrete recurrent constituents: clustering and boundary-finding mechanisms. Clustering mechanisms are based on identifying frequently co-occurring elements and merging them together as parts that form a single constituent. Bracketing (or boundary-finding) mechanisms work by identifying rarely co-occurring elements that correspond to the boundaries between discrete constituents. In a series of behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Statistical learning includes a set of mechanisms that are differentially engaged in different domains and modalities (Conway, 2020; Polyanskaya, 2021; Siegelman et al, 2017; Thiessen et al, 2013), while metacognitive processes monitor the performance of these underlying cognitive mechanisms on a case-by-case (or mechanism-by-mechanism) basis. We did not observe any correlation between the metacognitive monitoring processes engaged by different modalities or domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical learning includes a set of mechanisms that are differentially engaged in different domains and modalities (Conway, 2020; Polyanskaya, 2021; Siegelman et al, 2017; Thiessen et al, 2013), while metacognitive processes monitor the performance of these underlying cognitive mechanisms on a case-by-case (or mechanism-by-mechanism) basis. We did not observe any correlation between the metacognitive monitoring processes engaged by different modalities or domains.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that an increase in the quantity of linguistic structures with no increase in the diversity of these structures may have a negative effect on metaefficiency, resulting in lower metacognitive processing skills in the visual modality. Statistical learning is not a single mechanism, but rather an ability that is served by a set of neuro-cognitive mechanisms (Conway & Christiansen, 2005, 2006; Frost et al, 2015; Polyanskaya, 2021; Thiessen et al, 2013). The differential effects of linguistic experience on metacognitive monitoring across perceptual modalities in our task could be due to the need to monitor different sets of cognitive mechanisms in the visual and auditory modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors have similarly found that adults can accurately identify familiar triplets over novel phantoms (Slone & Johnson, 2015). On balance, most experiments have found that participants can discriminate words from phantom sequences Perruchet & Poulin-Charronnat, 2012;Polyanskaya, 2022;Slone & Johnson, 2015, with a small number of studies reporting null results (Endress & Langus, 2017;Endress & Mehler, 2009). We, therefore, use the finding that participants show a preference for words over phantom words as our target result.…”
Section: Study 8: Words Vs Phantom Wordsmentioning
confidence: 98%
“…Participants have also shown stronger preferences for words than "phantom" sequences that have identical TPs but never appeared in the exposure language Perruchet & Poulin-Charronnat, 2012;Polyanskaya, 2022;Slone & Johnson, 2015cf. Endress & Langus, 2017;Endress & Mehler, 2009).…”
Section: Statistical Learning and Word Discoverymentioning
confidence: 99%
“…Revista de Investigación en Ciencia de la Educación / Volumen 8, Nro. 33 / abril-junio 2024 ISSN: 2616-7964 / ISSN-L: 2616-7964 / www.revistahorizontes.org al., 2020); trabajar la conciencia silábica implico desarrollar la conciencia visual y auditiva de tonos y alargamiento de sílabas; la memoria ordinal y de encadenamiento para identificar el orden secuencial de las sílabas y su segmentación(Polyanskaya, 2021); incluso pre escolares con TEA desarrollaron la identificación inicial, final, la omisión o sustitución de silabas de palabras en una lectura(Azcárraga et al, 2022); además, el acento silábico permitió al receptor reconocer en las palabras y frases los límites, el sentido, la información y ampliar la expresión a un contexto más amplio(Holopainen et al, 2020); recomendando trabajar oportuna y adecuadamente la conciencia silábica para superar deficiencias que pudieran impedir una lectura comprensiva y asertiva (A Khan y Bajre, 2018)(Justi et al, 2021), para desarrollarla se recomienda trabajar la memoria semántica, la forma y las representaciones detalladas de las palabras (Janssen et al, 2019), así como el significado del vocabulario para percibir, representar, decodificar y entender palabras y oraciones (Zhang et al, 2021), permitiendo comprender textos y hacer correcto uso de las palabras en las frases que empleamos (Bassani y Soares, 2022); interviniendo en el aprendizaje de la lectura, dándole sentido al texto incluso en estudiantes bilingües, identificando el lenguaje y habilidades a trabajar para desarrollar la conciencia fonológica (Jasińska y Petitto, 2018); además los trastornos del desarrollo y sensoriales pueden afectar el desarrollo de los niveles léxico semántico en el reconocimiento de las palabras o unidades léxicas (Nittrouer et al, 2018), por loque se recomienda realizar tareas de organización auditivas acompañadas conimágenes(Coch, 2018).Se reconoció la importancia de la Conciencia Morfológica, en la adquisición de los elementos del lenguaje oral, la decodificación de los primeros estadios de lectura, en la capacidad de derivar palabras a partir de otras, que contribuyen en la comprensión lectora(Colé et al, 2018), desarrollando la conciencia morfológica flexiva de una lengua ligada a la estructura sintáctica, antes que los morfemas derivativos(Lázaro et al, 2021), los lectores principiantes mantienen intactas las estructuras morfológicas de los verbos pasivos, reflexivos, pero, aún no interpretan aquellos con mayor carga sintáctica, que permita encontrar en el verbo información del sujeto (número, persona, género, tiempo y aspecto), ni formar palabras nuevas adicionando un sufijo a una palabra existente(Nerantzini et al, 2022), encontraron que muchos problemas del lenguaje comprensivo desde la perspectiva de maestros radican en el vocabulario, la sintaxis y la reflexión sobre la formación de las palabras y sus reglas así como la manipulación de las estructuras morfológicas que las componen(Ralli et al, 2022); aseguran que es importante en preescolar, pero fundamental en laValle-Zevallos M. y cols.…”
unclassified